Palliative care and the growing health needs of older people in Poland - Drop, Bartłomiej; Barańska, Agnieszka; Firlej, Ewelina; Janiszewska, Mariola; Jędrych, Marian (Journal of Education, Health and Sport, 2017)
The development of medicine and new technologies allows for more effective disease diagnosis and early treatment. Life time was significantly extended for both men and women. Society in Poland and other European countries is aging. The number of people in working age is declining, while the proportion of the oldest age groups is increasing. The aging process is accompanied by an increase in the incidence of senile diseases, chronic diseases such as malignant diseases. The purpose of palliative care is to improve the quality of life of a chronically ill person and family. Palliative care is a holistic approach to the patient, focuses on alleviating suffering, pain, and eliminating psychological, social and spiritual problems. Unfortunately, access to palliative and hospice benefits is still insufficient. Waiting time for health services and especially palliative and hospice care exceeded the socially and medically unacceptable level. Health education is needed to target chronically ill persons, their families and the general public to explain the substance of palliative care, opportunities and what it offers. It is essential for the European countries to respond to the growing health needs of seniors. The reorganization of the health sector should be at local, regional and national levels.